2016
DOI: 10.1155/2016/8951053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Limbal and Pars Plana Approaches Using Microincision Vitrectomy for Removal of Congenital Cataracts with Primary Intraocular Lens Implantation

Abstract: Purpose. To compare the surgical outcomes of limbal versus pars plana vitrectomy using the 23-gauge microincision system for removal of congenital cataracts with primary intraocular lens implantation. Methods. We retrospectively reviewed all eyes that underwent cataract removal through limbal or pars plana incision. Main outcome measures included visual outcomes and complications. Results. We included 40 eyes (26 patients) in the limbal group and 41 eyes (30 patients) in the pars plana group. The mean age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
9
0
5
Order By: Relevance
“…The higher vitreous pressure observed in infants might explain why they experience more postoperative complications following surgery using a corneal approach. Using a 23-gauge vitrectomy, Lui et al 14 also compared different approaches for primary intraocular lens (IOL) implantation in the bag or in the ciliary sulcus. The authors observed greater numbers of intraoperative and postoperative complications, and a greater number of additional surgeries were performed for patients who underwent surgery using the limbal approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher vitreous pressure observed in infants might explain why they experience more postoperative complications following surgery using a corneal approach. Using a 23-gauge vitrectomy, Lui et al 14 also compared different approaches for primary intraocular lens (IOL) implantation in the bag or in the ciliary sulcus. The authors observed greater numbers of intraoperative and postoperative complications, and a greater number of additional surgeries were performed for patients who underwent surgery using the limbal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Primary IOL implantation has become more frequent, and research is ongoing to identify better treatments for pediatric cataracts. The literature reports few results comparing surgical approaches, and most of these studies have short-term follow-up periods 14,15. Additional reports are needed to explore the long-term complications in this age group because postoperative complications should be monitored in children throughout life 16,17.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who were clinically diagnosed with CC from June 2018 to May 2019 were recruited. All patients underwent a detailed ophthalmic examination, including slit-lamp examination, B ultrasound, intraocular pressure measurement, and ultrasonic A-scan, as mentioned in our previous study [20]. Visual acuity (VA) was recorded in all patients who were able to cooperate.…”
Section: Clinical Evaluations and Sample Collectionmentioning
confidence: 99%
“…All patients underwent a detailed ophthalmic examination, including slit-lamp examination, B ultrasound, intraocular pressure measurement, and ultrasonic A-scan, as mentioned in our previous study. (20) Visual acuity (VA) was recorded in all patients who were able to cooperate. Patients diagnosed with monocular CC additionally underwent post-eyeball color Doppler ultrasound to help in the differential…”
Section: Clinical Evaluations and Sample Collectionmentioning
confidence: 99%